Factors affecting attendance to cervical cancer screening among women in the Paracentral Region of El Salvador: a nested study within the CAPE HPV screening program. (December 2015) - Alfaro, Karla; Gage, Julia; Rosenbaum, Alan; Ditzian, Lauren; Maza, Mauricio; Scarinci, Isabel; Miranda, Esmeralda; Villalta, Sofia; Felix, Juan; Castle, Philip; Cremer, Miriam
Abstract Background Cervical cancer is the third most commonly occurring cancer among women and the fourth leading cause of cancer-related deaths in women worldwide, with more than 85 % of these cases occurring in developing countries. These global disparities reflect the differences in cervical cancer screening rates between high-income and medium- and low-income countries. At 19 %, El Salvador has the lowest reported screening coverage of all Latin American countries. The purpose of this study is to identify factors affecting public sector HPV DNA-based cervical cancer screening participation in El Salvador. Methods This study was nested within a public sector screening program where health promoters used door-to-door outreach to recruit women aged 30–49 years to attend educational sessions about HPV screening. A subgroup of these participants was chosen randomly and questioned about demographic factors, healthcare utilization, previous cervical cancer screening, and HPV knowledge. Women then scheduled screening appointments at their public health clinics. Screening participants were adherent if they attended their scheduled appointment or rescheduled and were screened within 6 months. The association between non-adherence and demographic variables, medical history, history of cancer, sexual history, birth control methods, and screening barriers was assessed using Chi-square tests of significance and logistic regression. Results All women (n  = 409) enrolled in the study scheduled HPV screening appointments, and 88 % attended. Non-adherence was associated with a higher number of lifetime partners and being under-screened—defined as not having participated in cervical cancer screening within the previous 3 years (p  = 0.03 andp  = 0.04, respectively); 22.8 % of participants in this study were under-screened. Conclusions Adherence to cervical cancer screening after educational sessions was higher than expected, in part due to interactions with the community-based health promoters as well as the educational session itself. More effective recruitment methods targeted toward under-screened women are required.